KOMUNIKASI LINTAS PERSPEKTIF (Hubungan Sains dan Agama) - Indira Syam (Jurnal Dakwah Tabligh, 2015)
There is a view in society that science and religion collide with each other so as to trigger the turmoil in society. Though both have a very significant role in human life. Science gives a lot of knowledge for humans. With the development of science, will promote the world with a variety of brilliant discoveries and provide convenience facilities were very supportive of human survival. Science and religion is said to be something different, because they have a different paradigm. Science and religion have in common, which aims to give peace. Religion provides peace of mind in terms because there is the promise of life after death, while science (science) give peace and at the same time for the ease of life in the world.